Analisis Kualitas Kalimat Majemuk pada Teks Eksplanasi di Website "Brainacademy" Edisi Agustus 2024 sebagai Kelayakan Bahan Ajar Membaca Kritis Bagi Siswa SMP - Harlin Nur Afizah; Inara Faridotu Rohmah; Khonitah Nuril Hidayati; Wafa Khoirunnisa; Mustofa Zaen Zakcy; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Anggit Wicaksono (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Explanation text is a text that can train critical reading skills, especially for junior high school students. It contains compound sentences that summarize information from several sentences into one sentence. Writing compound sentences that are not quite right will also affect the meaning or meaning that will be conveyed in the explanation text. The purpose of this study was to determine the quality of compound sentences in the explanation text which will later be used as teaching materials for junior high school students. The quality of good compound sentences will later affect students' critical reading skills. The methodology used is a qualitative approach where data collection is carried out first. This technique is carried out using the Listen and Note technique. The Listen technique is done by reading and observing the explanation text on the brainacademy website. The note technique is carried out after reading the entire text recording the existing compound sentences and then re-identifying the results that have been obtained. After analyzing the explanation text, compound sentences of equal value and compound sentences of levels were found in the explanation text. The difference between the two sentences can be seen in the sentence structure and the use of conjunctions. The quality of compound sentences is also analyzed in terms of clarity of meaning, use of appropriate conjunctions, and level of complexity. The results of this study are expected to be a reference for teaching materials and provide insight into the influence of compound sentences that affect the quality of students' critical reading.